2002
DOI: 10.1116/1.1524151
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy of endohedral metallofullerene Lu–C82 on C60 film

Abstract: Articles you may be interested inThermal stability of surface freezing films in Ga-based alloys: An x-ray photoelectron spectroscopy and scanning tunneling microscopy study Wurtzite GaN surface structures studied by scanning tunneling microscopy and reflection high energy electron diffraction J.Endohedral metallofullerene Lu-C 82 molecules adsorbed on C 60 film have been investigated by an ultra-high-vacuum scanning tunneling microscopy. The C 60 film was obtained by depositing 2-3 ML of C 60 molecules on a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Organized fullerene nanostructures, as a unique platform for supramolecular chemistry 15,16 and as a resistive mask for photolithography when polymerized 17 are of great interest. Organized fullerene nanostructures, as a unique platform for supramolecular chemistry 15,16 and as a resistive mask for photolithography when polymerized 17 are of great interest.…”
mentioning
confidence: 99%
“…Organized fullerene nanostructures, as a unique platform for supramolecular chemistry 15,16 and as a resistive mask for photolithography when polymerized 17 are of great interest. Organized fullerene nanostructures, as a unique platform for supramolecular chemistry 15,16 and as a resistive mask for photolithography when polymerized 17 are of great interest.…”
mentioning
confidence: 99%
“…3,12 The adsorption characteristics are different from those of Lu@C 82 on a C 60 film, in which an accumulation of Lu@C 82 molecules is observed near the step edge. 5 The Dy@C 82 molecules neither migrate toward the step edge nor make significant clusters even after the substrate was heated up to 200°C; the STM image was measured at 295 K after annealing. These results imply that Dy@C 82 molecules are strongly bound by the Si surface.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the adsorption characteristics of metallofullerenes on semiconductor surfaces have been studied extensively by STM. [2][3][4][5][6] A STM image of Sc 2 @C 84 adsorbed on Si(100)-(2ϫ1) surface was first reported by Shinohara et al and showed a nearly spherical structure of the Sc 2 @C 84 molecule. 2 The first layer of Sc 2 @C 84 was not ordered, owing to strong interactions between the surface and the molecules.…”
Section: Introductionmentioning
confidence: 88%
“…Shi et al investigated Tb@C 82 molecules adsorbed on Si(100) 2 × 1 surface and the C 60 film with an ultrahigh vacuum scanning tunneling microscope (UHV-STM) [18]. It was found that the Tb@C 82 molecules were randomly distributed on the surface of Si(100) but form a close-packing monolayer on the C 60 film.…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes with metal atoms encapsulated (endohedral metallofullerenes) are novel forms of fullerene-based materials [18][19][20]. Shi et al investigated Tb@C 82 molecules adsorbed on Si(100) 2 × 1 surface and the C 60 film with an ultrahigh vacuum scanning tunneling microscope (UHV-STM) [18].…”
Section: Introductionmentioning
confidence: 99%